PENGEMBANGAN MEDIA POP UP BOOK PADA MATERI DONGENG - Chatrin Agist Savira; Widya Handayani; Masnunah Masnunah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The aim of this research is to develop Pop Up Books on Fairytale Materials. The goal of the researchers to develop the media in order to facilitate the students in the learning process. Research methods use R&D (Research and Development) methods, with descriptive techniques. There are three results of expert validation, a) material experts in obtaining a score of 100% with a description of Very Good, b) media experts in getting a rating of 92% with a statement of Very good, c) designers in getting the score of 86% with the description Of Very Good. And there are 2 scales, a small scale test of 3 pupils and a large scale of 1 class of 29 pupils. Data collection using hoist. Data analysis using percentage analysis. The results of the study, are a) that in the small-scale group trial the average of 94% of this means that the product belongs to the category Very Good. whereas of the large-scala trial has an average of 92.06% with a description Very Good. b) The practicality test of the pupils on the product Media Pop Up Book given to the researchers in learning belonged to Very High, this is proved by the percentage of answers angket pupils 93.18%. Keywords: Development, Media pop up book, Storytelling material. ABSTRAK Tujuan dalam penelitian ini adalah mengembangkan Pop Up Book Pada Materi Dongeng. Tujuan peneliti mengembangkan media tersebut agar memudahkan peserta didik dalam proses pembelajaran. Metode penelitian menggunakan metode R&D (Research and Development), dengan teknik deskriptif. Terdapat tiga hasil validasi ahli, a) ahli materi di peroleh nilai 100% dengan keterangan Sangat Baik, b) ahli media di peroleh nilai 92% dengan keterangan Sangat Baik, c) ahli desain di peroleh nilai 86% dengan keterangan Sangat Baik. Dan terdapat 2 skala, uji skala kecil berjumlah 3 peserta didik dan skala besar berjumlah 1 kelas yaitu 29 peserta didik. Pengumpulan data menggunakan angket. Analisis data menggunakan analisis persentase. Hasil penelitian, adalah a) Bahwa dalam uji kelompok skala kecil rata-rata sebesar 94% hal tersebut bermakna bahwa produk termasuk kedalam kategori Sangat Baik. Sedangkan dari uji skala besar memiliki rata-rata 92,06% dengan keterangan Sangat Baik. b) Uji Kepraktisan peserta didik terhadap produk Media Pop Up Book yang diberikan peneliti dalam belajar tergolong Sangat Tinggi, hal tersebut dibuktikan dengan persentase jawaban angket peserta didik 93,18%. Kata Kunci : Pengembangan, Media pop up book, Materi Dongeng